Offshore wind power policies and green total factor productivity: empirical evidence from coastal China - Zhang, Junjie; Wei, Zhuxia (Frontiers in Ecology and Evolution, 2023)
Introduction Green and high-quality development requires the transformation and upgrading the energy structure. As a clean and efficient new energy, the development of offshore wind power is related to the achievement of green development and the realization of the dual carbon goals. Methods Based on the perspective of green total factor production, this study aims to explore the impact of offshore wind power policies (OWPPs) on green and high-quality development. Taking 11 coastal areas of China from 2004 to 2020 as samples, this paper empirically tested the impact of OWPPs on green total factor productivity (GTFP) by using propensity score matching difference-in-differences method (PSM-DID). Results and discussion The results show that OWPPs have a significant positive impact on GTFP. The robustness test further verifies the results, and the provincial difference is significant. By stimulating technological innovation and reducing energy intensity, OWPPs have improved GTFP, but increasing marketization level is a long way off.